Surgical Outcomes of Temporary Ileostomy Patients attended at a Tertiary Care hospital in Dhaka City - Haque, Muhammad Faridul; Syeed-Ul-Alam, SM; Rahman, Ayesha; Khan, Md. Mahfuzur Rahman; Haque, Muhammad Enamul (Journal of Current and Advance Medical Research, 2021)
Background: Management of temporary ileostomy cases is very important considering the outcomes. Objective: The purpose of the present study was to observe the surgical complications of temporary ileostomy patients. Methodology: This prospective cohort study was conducted in the Department of Surgery at Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh over a period of six months from July, 2011 to December, 2011. All patients who had undergone temporary ileostomy after admission were selected as the study population. Patients with temporary ileostomy at any age in both male and female were included in this study. The surgical complications like prolapse, retraction, stenosis, necrosis, skin excoriation, parastomal hernia, bleeding and wound infection were recorded. Result: A total number of 100 patients were selected for observation and management of complications of temporary ileostomy. Their ages ranging from 15 to 65 years with mean age 33.9±11.92 years. Complications were developed in majority cases of cases (52.0%). Several systemic complications were recorded like electrolytes imbalance (31%), hypoproteinaemia (14%), RTI (6%) and significant weight loss (4%). Skin excoriation was the more frequent local complication developed in 32 (32%) patients. However, 36 patients developed laparotomy wound related complication. Conclusion: In conclusion high frequency of complications are found among the temporary ileostomy patients. Journal of Current and Advance Medical Research, January 2021;8(1):65-69